The Comparison of the Criminal Code and Draft Criminal Code Formulations of Crimes against Religion and Religious Life - Septa Candra; Chairul Huda (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
The formulation of criminal acts against religion and religious life in Indonesian laws and regulations still leaves various problems. This article discusses the form of formulation of criminal offenses against religion and religious life in the upcoming Criminal Code and RKUHP. The form of this research is normative juridical with legal, conceptual and case approaches. The results of this study indicate that the RKUHP has made changes that lead to